Sosio-Historis Pendidikan Islam Di Indonesia Pada Era Orde Baru - Misyroh Akhmadi (Universitas Alma Ata, 2013)
The new order era efford’s to improve the quality of human resources is done through the development of alignment between islamic schools (madrasah) and schools. The reign of new order era beginning with the collapse of the old order to do some serious efforts to improve the alignment. This paper will explaint the development of Islamic education in the new order era in the socio-historical context. Writing begins with the reign of the early efforts of the new order era in making policies to align islamic schools and schools. It was developed with the implementation of the policy of the new order era to improve the quality and quantity of viable islamic shools that align with the school on a variety of dimensions. The lates, be concluded with the results of development policies on the quality and quantity of the various dimensions of the islamic school, either in the curriculum or civil effect causes. Keyword; Islamic education, sosio –history contect